Regeneration failure of Scots pine changes the species composition of young forests - Ara, Mostarin; Barbeito, Ignacio; Kalén, Christer; Nilsson, Urban (2022)
How seedling mortality and browsing affects species composition of regenerating forests has been mostly studied on a small scale. Yet, large-scale analyses based on extensive data are essential for robust prediction of species composition in young forests. In this study, we used a dataset from a national inventory of young forests (1-4 metres in height) to investigate the species composition of young forests across Sweden. We found that most of the regenerated forest area (almost 90%) was planted with Norway spruce (southern Sweden) and Scots pine (northern Sweden). Regeneration of Norway spruce was generally relatively successful but as a consequence of seedling mortality and browsing, almost 40% of the area regenerated with Scots pine will probably not develop into pine-dominated stands. Thus, low survival of Scots pine seedlings and trees can profoundly change the trajectory of species composition of the young forest from what was originally intended, and a large proportion of the young stands may develop into mixtures of conifers and broadleaves. While such mixtures may benefit certain biodiversity and ecosystem services, a loss of Scots pine dominated stands may also have adverse impacts on the economic returns as well as pine-dependent biodiversity and recreational values.